THE EFFECTIVENESS OF DIGITAL-BASED E-TAX COURT SERVICES AT THE INDONESIAN TAX COURT: A DIGITAL GOVERNANCE ANALYSIS - Neni Triana; Florentina Ratih Wulandari; Muhamad Nur Afandi (RADJA PUBLIKA, 2026)
Digitalization of public services has encouraged government institutions to develop electronic-based services to improve efficiency, accessibility, and transparency. However, the availability of digital platforms does not always indicate that services have achieved optimal performance. This study aims to analyze the effectiveness of e-Tax Court services at the Indonesian Tax Court using a digital governance perspective. This research employs a qualitative descriptive approach. Data were collected through semi-structured interviews with four users of e-Tax Court, consisting of Appellants/Claimants and Respondents, supported by document analysis. Data analysis was conducted using the Miles, Huberman, and Saldana qualitative analysis model. The evaluation uses five dimensions developed by Holzer and Manoharan: security/privacy, usability, content, services, and citizen and social engagement. The findings indicate that e-Tax Court has improved tax dispute administration by simplifying procedures and reducing physical processes. Nevertheless, several challenges remain, particularly regarding users’ concerns about data protection, system responsiveness, accessibility, and limited feedback mechanisms. The study concludes that e-Tax Court has supported digital judicial transformation, but continuous improvement is required to create a more secure, inclusive, and user-oriented digital service.